Decision-Making about the Place of Death for Cancer Patients: A Concept Analysis - Yoko Minamiguchi (Elsevier, 2020)
Objective: The objective of the study was to conduct a concept analysis of "decision-making about the place of death for cancer patients" to develop a theoretical definition of the concept and identify its attributes, antecedents, and outcomes. Methods: The Rodgers' evolutionary model of concept analysis was used. A literature search for papers published from 2000 to 2017 was conducted using the keywords: "cancer," "place," "death," and "decision-making" for the search of the electronic databases. Results: Thirty articles were selected for this analysis. As a result, five attributes, six antecedents, and five consequences were extracted. [options to choose as a place of death], [wishes of the patients themselves], [consideration of the burden on the family], [open discussions with other persons concerned], and [best choice according to circumstances] are considered to be the characteristics in the decision-making about the place of death for cancer patients. Conclusions: This concept is defined as "The best choice according to circumstances of the cancer patients among different options for a place of death, resulting from a careful evaluation of the wishes of these patients and the burden on the family, as well as through open discussions with other persons concerned." Nurses need to assist patients discuss deaths with important others, such as family members, in making decisions about the place of death. Further studies are necessary to elucidate the details of the categories and relationships shown in the attributes in this study, investigating the actual conditions of the patients and their families.